Principles of Penal Procedures Against Legal Persons - Kolaković-Bojović, Milica (Zbornik Instituta za kriminološka i sociološka istraživanja, 2012)
The artificial nature of a legal person requires that the form and scope of fundamental principles of penal procedures be adapted to unique proceedings against corporations and their employees. These modifications affect mostly prosecution principles. Accordingly, the author bases her article on that issue, considering the fact that the legal system of the Republic of Serbia has three categories of corporate liability. In which conditions can the prosecutor depart from the unique procedure principle? Is there any possibility for penal liability of a legal person in situations where the identity of a natural person is unknown? How does the unique procedure principle affect the double jeopardy principle? These are only a small part of the issues that the author considers.